Gyrotactic microorganism and bio-convection during flow of Prandtl-Eyring nanomaterial - Hayat Tasawar (De Gruyter, 2021)
Our main intension behind this work is to investigate Prandtl-Eyring nanomaterial in presence of gyrotactic microorganisms. Flow is generated via stretching sheet and is subject to melting heat effect. Radiation and dissipation are addressed. Entropy rate is also reported. Nanofluid effects are explored through Buongiorno model for nanofluid by considering Brownian motion and thermophoresis impacts. Problem related modelling is done by obtaining PDEs and these PDEs are then transmitted into ODEs by using appropriate similarity variables. Homotopic technique has been employed to obtain a convergent series solution of the considered problem. Graphical results have been presented to investigate the impact of different prominent variables over fluid velocity, temperature distribution, nanofluid concentration and on microorganism concentration. Entropy analysis has been discussed and the physical quantities such as surface drag force, Nusselt number, local Sherwood number and microorganism density number for the current problem is obtained. Velocity boost against higher melting and fluid parameters. Temperature of the fluid reduces with an increment in melting and radiation parameters while it intensifies through Prandtl and Eckert number, Brownian motion and thermophoresis parameters. Decay in concentration is noticed against higher values of melting and thermophoresis parameters while it increases for higher Schmidt number and Brownian motion parameter. Microorganism field boosts with higher values of Peclet number and microorganism concentration difference parameter. Moreover entropy generation rate intensifies against higher radiation parameter and Brickman number.